THE NATIONAL POLICY PURSUED BY THE SOVIET GOVERNMENT IN THE FIELD OF CULTURE IN UZBEKISTAN, AND ITS SOCIAL CONSEQUENCES (1945-1960) (Scientific journal of the Fergana State University, 2026)
This article examines the development of culture and literature in Uzbekistan under the influence of communist ideology after World War II. Additionally, it analyzes the efforts to glorify national values and Uzbek national heroes, as well as the movement to revive national identity in literature. It is noted that many Uzbek writers were accused of excessive idealization of the past instead of reflecting communist reality in their works. The Soviet ideology sought to completely subordinate Uzbek literature to communist ideas. A particularly concerning aspect of this process was the strict censorship of childrenʼs literature, which was subjected to ideological control and infused with communist propaganda. The study analyzes how one of the primary goals of this process was to suppress the spirit of the peopleʼs aspiration for independence. Furthermore, the loss of national dramatic art forms and the disappearance of unique theatrical traditions are emphasized. The research includes a comparative analysis of the works of national, Western, and Russian scholars addressing this topic.